Cannabinoids, the endocannabinoid system, and pain: a review of preclinical studies. (July 2021) - Finn, David P.; Haroutounian, Simon; Hohmann, Andrea G.; Krane, Elliot; Soliman, Nadia; Rice, Andrew S.C.
Abstract : Abstract: This narrative review represents an output from the International Association for the Study of Pain's global task force on the use of cannabis, cannabinoids, and cannabis-based medicines for pain management, informed by our companion systematic review and meta-analysis of preclinical studies in this area. Our aims in this review are (1) to describe the value of studying cannabinoids and endogenous cannabinoid (endocannabinoid) system modulators in preclinical/animal models of pain; (2) to discuss both pain-related efficacy and additional pain-relevant effects (adverse and beneficial) of cannabinoids and endocannabinoid system modulators as they pertain to animal models of pathological or injury-related persistent pain; and (3) to identify important directions for future research. In service of these goals, this review (1) provides an overview of the endocannabinoid system and the pharmacology of cannabinoids and endocannabinoid system modulators, with specific relevance to animal models of pathological or injury-related persistent pain; (2) describes pharmacokinetics of cannabinoids in rodents and humans; and (3) highlights differences and discrepancies between preclinical and clinical studies in this area. Preclinical (rodent) models have advanced our understanding of the underlying sites and mechanisms of action of cannabinoids and the endocannabinoid system in suppressing nociceptive signaling and behaviors. We conclude that substantial evidence from animal models supports the contention that cannabinoids and endocannabinoid system modulators hold considerable promise for analgesic drug development, although the challenge of translating this knowledge into clinically useful medicines is not to be underestimated.